Water-Mediated Green and Efficient Synthesis of Bis(Indolyl)methanes Using Ammonium Iron(II) Sulfate - Kadu, Vikas D.; Nadimetla, Dinesh N.; Hublikar, Mahesh G.; Raut, Dattatraya G.; Bhosale, Raghunath B. (Letters in Organic Chemistry, 2020)
An efficient protocol for the synthesis of symmetrical 3,3’-bis(indolyl)arylmethanes catalyzed by green and easily available ammonium iron(II) sulfate (Mohr’s salt) has been developed in “green” water solvent afforded in excellent yield.
Keywords: Bis(indolyl)methanes